Trust and Transparency: Perspectives upon the Communication of the National Bank of Romania during the Financial Crisis - IACOB, Raluca (Management Dynamics in the Knowledge Economy, 2018)
The financial crisis that started in 2008 embodies the failure of a system whose most vulnerable point was detected within the banking sector. The increasing loss of trust in the most important institutions of this sector throughout the crisis led to a gap between the perception of the financial industry representatives and that of the people outside it. At the same time, the crisis triggered the reconfiguration of the means used to maintain both financial, and price stability, and redesigned the role and strategy of central banks in using monetary policy tools, including communication. After 2008, central banks resorted to aggressive, sometimes unconventional monetary policies. Whether bringing interest rates close to zero or on negative territory, adopting quantitative easing measures or practicing forward guidance, central banks communicated more extensively as compared to the period prior to the crisis. While no consensus has been yet reached regarding the usefulness of these measures, researchers consider that some of them will become part of the usual toolkit used by central banks, which will further intensify their communication activity. This paper is a qualitative research that analyses the perception of the National Bank of Romania’s representatives – communication specialists and officials who were highly visible in the mass-media during that specific period – upon the loss of public trust in the central bank. At the same time, the interviews reflect the perception of the central bank’s representatives upon the effects of making the monetary policy more transparent during the period considered, and examine to what extent the chosen communication decisions can be reversible after surmounting the financial crisis, on an emerging market where no other unconventional monetary policy measures had been used.